The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.33271/mining16.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical pollution peculiarities of the Nadiya mine rock dumps in the Chervonohrad Mining District, Ukraine

Abstract: Purpose. The research purpose is to study the peculiarities of chemical pollution of the Nadiya mine rock dumps in the Chervonohrad Mining District, depending on the relief conditions and slope exposure, as well as to analyze the general trends in the distribution of chemical elements compared to the natural background. Methods. The chemical pollution differentiation of the Nadiya mine rock dumps at the level of ecotopes is studied on the basis of dispersion analysis; multidimensional ordination of ecot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The previous studies had shown that the anthropogenic activities were associated with higher concentrations of heavy metals in the river [49][50][51]. In addition to agricultural activities and domestic sewage discharge, mining is one of the important sources of heavy metal pollutants [52,53], and the dumps located around abandoned mining sites are also potential sources of contamination [54][55][56]. In the BR basin, a variety of mineral resources such as copper, nickel, and polymetal are distributed, which may be one of the main reasons for the prominent heavy metal pollution in the river water of the basin under the runoff action.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies had shown that the anthropogenic activities were associated with higher concentrations of heavy metals in the river [49][50][51]. In addition to agricultural activities and domestic sewage discharge, mining is one of the important sources of heavy metal pollutants [52,53], and the dumps located around abandoned mining sites are also potential sources of contamination [54][55][56]. In the BR basin, a variety of mineral resources such as copper, nickel, and polymetal are distributed, which may be one of the main reasons for the prominent heavy metal pollution in the river water of the basin under the runoff action.…”
Section: Discussionmentioning
confidence: 99%
“…The dump covers an area of 24.07 hectares and stores 13.5 million tons of waste rocks. Thus, at a bulk density of 2.5 t/m 3 , they form an actual piled dump volume of 5.4 million m 3 . Study of the data for the area under the dump in Google Earth software shows a match with the actual 24.07 hectares, and the dump height data of 40 m is not comparable to the actual data, since the data is not publicly available.…”
Section: Determining the Predicted Volumes Of Mine Waste Rock Dumpsmentioning
confidence: 99%
“…Mining industry is the driving force in the development of the economies of many countries around the world, contributing significantly to foreign exchange budget revenues. However, the functioning of mining enterprises greatly pollutes the natural environment [1][2][3]. The upper earth crust layer suffers the greatest damage, since millions of cubic meters of minerals and waste rocks are removed from the depths by underground and surface methods, disturbing the natural balance and hydrogeological regimes of ground and surface waters [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental problems are most often caused by facilities built in the previous century, at a time when less attention was paid to environmental issues. Numerous studies from around the world have shown the negative impact of mining waste on the environment through the distribution of microelements in soil and groundwater [14,15].…”
Section: Introductionmentioning
confidence: 99%